CAUSATIVE VARIABLES FOR DROP-OUT AND SUGGESTIONS FOR RETENTION OF STUDENTS IN HOME/ COMMUNITY SCIENCE - RAGINI RANAWAT* and SHATAKSHI SEMWAL, (The Journal of Research ANGRAU, 2020)
The research (conducted under the ICAR funded extramural project) was carried out purposively withthe college students and faculty staff selected from Home/Community Science colleges/departments from sixuniversities across five states to find out the causative variables that have an impact on the enrolment percentagein Home/Community Science. The information was collected through an online Google form, from a total of166 students and 51 faculty staff, respectively. According to the respondents, inactive placement cell (66.3%students & 56.9% faculty staff), lack of collaboration with the industries, institutions, and universities (48.2%students) and less dynamic practical classes linked to job providers (49.4% students & 49% faculty staff)were the major causes that lead to student drop-outs. Furthermore, the suggestions for retention of studentspertained to holding open sessions on career opportunities and higher studies (65.7% students), regularorientations among students and industry representatives (57.8% students), and publicity of the subject throughonline media platforms (88.2% faculty staff) promotes effective and efficient working. It was clear from thestudy that there is a need to upgrade the operation of Home/Community Science education.